ChemInform Abstract: Synthesis of ortho‐Acylphenols Through the Palladium‐Catalyzed Ketone‐Directed Hydroxylation of Arenes. Issue 20 (25th April 2013) - Mo, Fanyang; Trzepkowski, Louis J.; Dong, Guangbin
Abstract The title reaction provides various 2‐acylphenols by using the complementary methods A) and B), and an unusual ketal‐lactone [viz.